Analisis dan Perancangan Prototype Sistem Antrian Online Berbasis Web untuk Layanan Bank - Pebi Mina Husania; Rani Chantika; Mhd. Furqan (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
This study focuses on the analysis and design of a web-based online queue system prototype for banking services, aiming to improve service quality and operational efficiency. In the banking sector, managing customer waiting times is a significant challenge that impacts their comfort and satisfaction. The online queue system enables customers to obtain queue numbers online, thereby minimizing waiting times and making queue management more efficient. This research includes system requirements analysis, user interface design, and process flow development tailored to customer needs and banking operations. The resulting prototype is expected to serve as a foundation for developing a more comprehensive digital queue system, supporting digital transformation in the banking sector, and providing practical and theoretical contributions to web-based service development.